2019
DOI: 10.3746/pnf.2019.24.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of 100% Flesh Watermelon [Citrullus lanatus (Thunb.) Matsum. and Nakai] Juice Improves Swimming Performance in Rats.

Abstract: Nutritional intervention of fruit juice supplementation is able to maximize exercise performance. Watermelon [Citrullus lanatus (Thunb.) Matsum. and Nakai] contains high L-citrulline content and consumption of watermelon juice may promote ergogenic effects. The aim of the present study was to investigate the role of 100% flesh watermelon juice and 100% rind watermelon juice supplementation for 14 days on swimming performance in rats. Twenty four male Sprague-Dawley rats were randomly divided into four groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
7
0
3
Order By: Relevance
“…Dalam 100 g buah semangka kurang lebih terkandung 10,82 g karbohidrat, 91% air, dan 182 mg kalium (Kardina, 2021). Bagian mesokarp (bagian berwarna putih, antara daging buah dan kulit) mengandung kurang lebih 45.02 mg/g sitrulin sementara bagian daging buah mengandung kurang lebih 43,81 mg/g sitrulin (Ridwan et al, 2019). Kandungan sitrulin pada semangka kuning lebih tinggi dibandingkan semangka merah (Duran Barón et al, 2021).…”
Section: Pendahuluanunclassified
“…Dalam 100 g buah semangka kurang lebih terkandung 10,82 g karbohidrat, 91% air, dan 182 mg kalium (Kardina, 2021). Bagian mesokarp (bagian berwarna putih, antara daging buah dan kulit) mengandung kurang lebih 45.02 mg/g sitrulin sementara bagian daging buah mengandung kurang lebih 43,81 mg/g sitrulin (Ridwan et al, 2019). Kandungan sitrulin pada semangka kuning lebih tinggi dibandingkan semangka merah (Duran Barón et al, 2021).…”
Section: Pendahuluanunclassified
“…7 The rind watermelon juice contains 45.02 mg/g Lcitrulline and flesh watermelon juice contains 43.81 mg/g. 8 Rind watermelon juice contains a higher L-citrulline content compared to flesh watermelon, and L-citrulline in yellow watermelons is higher than red watermelons. 9 Nevertheless, the findings may suggest that both flesh and rind watermelon juices potentially offer similar benefits to pure L-citrulline for improving exercise performance.…”
Section: Introductionmentioning
confidence: 96%
“…10 A study by Ridwan, et al, showed that supplementation with 100% flesh watermelon juice improves endurance in swimming performance in rats. 8 Another type of fruit that has a beneficial effect as nutritional ergogenics is plantain. Plantain is one type of banana fruit, contains about 31.15 g of carbohydrates and 564 mg potassium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both foods have been previously reported to help improve exercise and training performance after ingestion. Plantain and yellow watermelon were known for endurance training improvement and muscle fatigue index due to their high citrulline contents [7], [8] However, not many studies have analyzed the effect of combined yellow watermelon-plantain juice toward blood glucose level and antioxidant effect during exercise.…”
Section: Introductionmentioning
confidence: 99%